مقومات حوكمة الشركات المساهمة في سورية من وجهة نظر المراجعين والمستثمرين - القاضي, حسين; البهلول, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
بحثت هذه الدراسة في مقومات حوكمة الشركات في سورية والعقبات التي تحول دون تطويرها، وذلك من خلال الاطلاع على أدبيات الحوكمة في الدول المتقدمة. وقد وضعت الدراسة 11 سؤالاً تتناول الجوانب التشريعية والتنظيمية لتشجيع حوكمة الشركات في سورية من خلال استعراض المقومات التي وضعتها هيئة الأوراق والأسواق المالية السورية بالإضافة إلى بعض المقومات الأخرى. وقد تم اختبار هذه المقومات من خلال استبيان تضمنت 12 سؤالاً وزع على عينتين، الأولى مثلت المحاسبين القانونين من غير العاملين في شركات المحاسبة الأربع الكبرى. أما العينة الثانية فقد تضمنت أعضاء من المنتسبين لغرفة صناعة دمشق نظراً لأهمية هذا الموضوع بالنسبة إليهم. وقد تم توزيع 100 استبانه على كل من المجتمعين. تم الحصول على 45 جواباً من المحاسبين القانونيين و 26 جواباً من أعضاء غرفة صناعة دمشق. وقد كانت الإجابات متفقة بصورة عامة مع ما ذهبت إليه الدراسة . This paper has investigated the Syrian corporate governance bases, and its development barriers, in the course of browsing the corporate governance literature in the developed countries. It has developed eleven questions dealing with different legislative and organizational aspects that might encourage the Syrian corporate governance. These aspects were derived from the bases developed by the Syrian Commission of Financial Markets and Securities and other sources. These bases were then tested using a twelve enquiries-based questionnaire which was distributed to two samples. The first represents the certified accountants excluding the big four accounting of importance to them. 100 questionnaires were distributed to both populations. 45 responses were received from the certified accountants and 26 from the members of Damascus Industry Chamber. Generally, the respondents' views of points were in conformity with the issues addressed by this paper.